2016
DOI: 10.1080/01647954.2015.1130941
|View full text |Cite
|
Sign up to set email alerts
|

Definition ofTenuipalpussensu stricto (Acari, Tenuipalpidae), with redescription ofTenuipalpus caudatus(Dugès) and description of a new species from Costa Rica

Abstract: The taxonomic history of the genus Tenuipalpus Donnadieu is discussed and Tenuipalpus caudatus (Dugès) (=Tenuipalpus palmatus Donnadieu) is redescribed based on specimens from Portugal intercepted at ports of entry in the United States, and references including photographic records of the neotype of T. caudatus. In addition, a proposed new species, Tenuipalpus erbei sp. nov. is described from Costa Rica. Our results show that T. caudatus, T. erbei sp. nov. and another 36 known species of Tenuipalpus share a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Beard et al 2014;Beard et al 2015;Castro et al 2016b;Tassi et al 2017;Welbourn et al 2017). The inclusion of morphological information regarding the eggs in future descriptions, for example as was provided in Beard et al (2014), Castro et al (2016a), Seeman et al (2016) and Welbourn et al (2017), may also contribute to our broader understanding of this family.…”
Section: Raoiella Pandanae Mohanasundaram Taxonomic Status Uncertainmentioning
confidence: 99%
See 1 more Smart Citation
“…Beard et al 2014;Beard et al 2015;Castro et al 2016b;Tassi et al 2017;Welbourn et al 2017). The inclusion of morphological information regarding the eggs in future descriptions, for example as was provided in Beard et al (2014), Castro et al (2016a), Seeman et al (2016) and Welbourn et al (2017), may also contribute to our broader understanding of this family.…”
Section: Raoiella Pandanae Mohanasundaram Taxonomic Status Uncertainmentioning
confidence: 99%
“…Lindquist (1985) provided an extremely detailed anatomical analysis of the Tetranychidae which has been used as a guide for the collection of information on representative tenuipalpid genera (e.g. Zhang & Fan 2004;Xu & Fan 2010;Seeman & Beard 2011;Xu et al 2013;Beard et al 2014Beard et al , 2016Castro et al 2015Castro et al , 2016aCastro et al , b, 2017Welbourn et al 2017). Lindquist (1985) places great significance on ontogenetic changes in leg chaetotaxy, pointing out that until the comparative homologisation of leg setae is accomplished for representative taxa within the Tetranychoidea, a great deal of character state data of potential significance to the systematics, phylogeny and classification of these groups will remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Adults female and male: Species of this group can be differentiated from other Tenuipalpus by presence of one pair of lateral body projections associated with setae c3. See Castro et al (2016) for a detailed diagnosis.…”
Section: Tenuipalpus Sensu Stricto Groupmentioning
confidence: 99%
“…The definition of Tenuipalpus sensu stricto (Acari: Tenuipalpidae) was based on the re-description of T. caudatus (Dugès), 1834 (= T. palmatus Donnadieu, 1876), and on the study of 37 other known species of Tenuipalpus (Castro et al 2016). These authors indicated the presence of one pair of lateral body projections associated with setae c3 as a synapomorphy for this group.…”
Section: Introductionmentioning
confidence: 99%
“…Tenuipalpus Donnadieu is the largest genus of this family with more than 300 species described (Mesa et al 2009;Castro et al 2016aCastro et al , 2017Welbourn et al 2017). Recently, after resurrecting Colopalpus (Castro et al 2015), Castro et al (2016b) proposed the division of Tenuipalpus in two groups: sensu stricto, a homogenous group with body projections associated with opisthosomal setae c3; and sensu lato, a heterogenous group without the body projections associated with setae c3.…”
Section: Introductionmentioning
confidence: 99%